The Effect of Leverage and Gender Diversity on Board of Directors to Tax Aggressivity - Sapta Setia Darma; Juniati, Emelia (Universitas Pamulang, 2024)
Tax aggressiveness refers to the company's reducing tax burden to be paid legally and illegally. This study aims to obtain empirical evidence regarding the influence of Leverage and Gender Diversity on the Board of Tax Aggressiveness. The research methodology employed quantitative research using secondary data from annual financial reports published on the Indonesia Stock Exchange (IDX) for companies in the property and real estate sector for 2017-2021. The sampling method utilized purposive sampling, resulting in a sample size of six companies with 30 data points. Data analysis techniques included the Chow test, Hausman test, and Lagrange multiplier test for model selection, in addition to descriptive statistical tests, classical assumption tests, and panel data regression analysis. The findings revealed that leverage and gender diversity on the board impacted tax aggressiveness. These results have implications for the Directorate General of Taxes (DGT) in detecting aggressive tax practices within companies.